A review of dietary phytochemicals and their relation to oxidative stress and human diseases. (May 2021) - Guan, Ruirui; Van Le, Quyet; Yang, Han; Zhang, Dangquan; Gu, Haiping; Yang, Yafeng; Sonne, Christian; Lam, Su Shiung; Zhong, Jiateng; Jianguang, Zhu; Liu, Runqiang; Peng, Wanxi
Abstract: Phytochemicals refer to active substances in plant-based diets. Phytochemicals found in for example fruits, vegetables, grains and seed oils are considered relatively safe for consumption due to mammal-plant co-evolution and adaptation. A number of human diseases are related to oxidative stress caused by for example chemical environmental contaminants in air, water and food; while also lifestyle including smoking and lack of exercise and dietary preferences are important factors for disease development in humans. Here we explore the dietary sources of antioxidant phytochemicals that have beneficial effects on oxidative stress, cardiovascular and neurological diseases as well as cancer. Plant-based diets usually contain phenolic acids, flavonoids and carotenoids, which have strong antioxidant properties, and therefore remove the excess of active oxygen in the body, and protect cells from damage, reducing the risk of cardiovascular and Alzheimer's disease. In most cases, obesity is related to diet and inactivity and plant-based diets change lipid composition and metabolism, which reduce obesity related hazards. Cruciferous and Allium vegetables are rich in organic sulphides that can act on the metabolism of carcinogens and therefore used as anti-cancer and suppressing agents while dietary fibres and plant sterols may improve intestinal health and prevent intestinal diseases. Thus, we recommend a diet rich in fruits, vegetables, and grains as its content of phytochemicals may have the potential to prevent or improve a broad sweep of various diseases. Graphical abstract: Image 1